Design of a fuzzy logic controller for regulating substrate feed to fed-batch fermentation - Hisbullah, -; Hussain, Mohd Azlan; Ramachandran, K.B. (Food and Bioproducts Processing, 2003)
Fuzzy logic control based on the Takagi-Sugeno inference method has been applied for the regulation of feed rate to a fed-batch fermentation process. The process chosen is the baker's yeast fermentation. The simulation results show that the conventional fuzzy logic controller produces oscillations in the process response. To improve the performance of the conventional scheme, implementation of adaptive and hybrid control schemes are proposed. Significant improvements in the controller performance could be achieved by combining these two approaches. The adaptive control scheme reduces severe oscillations and the hybrid control scheme enhances control precision.